Correlation of cumulative corticosteroid treatment with magnetic resonance imaging assessment of avascular femoral head necrosis in patients with multiple sclerosis - Nilufer Kale; Jale Agaoglu; Osman Tanik (MDPI AG, 2010)
Increased risk of osteoporosis, fractures, and avascular necrosis (AVN) has been suggested in multiple sclerosis (MS). Patients with MS are often exposed to corticosteroid treatment (CST) during the disease course and conflicting reports exist regarding complications of CST. Our study aims to investigate the association between cumulative doses of CST and radiographic evaluation of AVN of the femoral head in MS. Twenty-six MS patients (mean age, 38.4±10 yr) were enrolled and prospectively evaluated for AVN by magnetic resonance imaging (MRI). The mean disease duration was 11.5±8.5 years and mean expanded disability status scale (EDSS) score was 3±2. The cumulative dosage of CST varied between 20 g and 60 g; patients were grouped into two categories: 1) CST between 20-40 g, 17 (65%) patients; 2) CST ≥40 g; 9 (35%) patients. The relationship between cumulative CST dosage and MRI diagnosis of AVN was statistically insignificant (P>0.9). Clarification of the cumulative effect of CST in the development of AVN is of great importance for future long-term steroid treatment strategies.